2005
DOI: 10.1002/jez.b.21066
|View full text |Cite
|
Sign up to set email alerts
|

Origination and innovation in the vertebrate limb skeleton: an epigenetic perspective

Abstract: The vertebrate limb has provided evolutionary and developmental biologists with grist for theory and experiment for at least a century. Its most salient features are its pattern of discrete skeletal elements, the general proximodistal increase in element number as development proceeds, and the individualization of size and shape of the elements in line with functional requirements. Despite increased knowledge of molecular changes during limb development, however, the mechanisms for origination and innovation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 129 publications
5
55
1
Order By: Relevance
“…Our results contribute to increasing evidence that activator-inhibitor interactions are involved in limb, digit and somite segmentation, and could reflect a universal design principle 4,[30][31][32][33][34][35] , but while confirmatory these results do not clarify the identity of the molecule(s) or the exact developmental mechanisms involved. We argue that the value of using the IC model is that, while previous models describe how segments form, they make no predictions about how they vary in size, and imply that elements are either independently formed or that segment proportions are largely the result of selection on later developmental events such as growth.…”
Section: Discussioncontrasting
confidence: 53%
“…Our results contribute to increasing evidence that activator-inhibitor interactions are involved in limb, digit and somite segmentation, and could reflect a universal design principle 4,[30][31][32][33][34][35] , but while confirmatory these results do not clarify the identity of the molecule(s) or the exact developmental mechanisms involved. We argue that the value of using the IC model is that, while previous models describe how segments form, they make no predictions about how they vary in size, and imply that elements are either independently formed or that segment proportions are largely the result of selection on later developmental events such as growth.…”
Section: Discussioncontrasting
confidence: 53%
“…Hosseini and Hogg (1991) also reported that chick embryos paralyzed with a DMB solution have shorter tibia owing to the reduction of formation of perichondral bone and cartilage. Reduction in size of long bones seems to be correlated with a reduction of embryonic movement, which leads to a decrease in Type II collagen, aggrecan, and glycosaminoglycan expression, and the consequent reduction of cartilage-matrix synthesis (Newman and Mü ller, 2005). Because the cartilaginous precursors of the carpal and tarsal elements also are diminished in size, it is thought that the same processes affect long bones and elements of the manus and pes.…”
Section: Discussionmentioning
confidence: 99%
“…), all of which are the same in vertebrates. In fact, many of the factors involved in vertebrate limb outgrowth and shaping (e.g., Dlx, Lmx, Hox, R-fng, Fgf, Shh, and Wnt) originated in ancestral metazoans, in which they also controlled tissue outgrowth and shaping (Newman and Mü ller, 2005). However, differences in the reactivity of the mesenchymal tissue to produce joints, and the threshold levels to respond to mechanical stress in sesamoid could constitute interesting variations to these highly conservative response patterns.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a plethora of fossil studies and experimental investigations in extant species (e.g., chicken), the formation of the broadest aspects of the shape of different skeletal elements and their basic spatial position has been mathematically modeled using activator-inhibitor systems (Hentschel et al 2004;Newman et al 2008;Newman and Müller 2005). This basic skeletal pattern in the adult organism is a fairly qualitative phenomenon and its developmental explanation involves quantitative models.…”
Section: Mathematical Models Of the Origin Of Morphological Structuresmentioning
confidence: 99%